The Influence of Literature Circles Group Discussion on English Reading Ability and Reading Attitudes for Senior High School Students - Chia-Yu Cho; Chao-Chen Chen (Tūzī yǔ dàng’àn xuékān, 2023)
The study analyzed the case of cooperative teaching in senior high school. The intention of this paper is to explore the learning method of literature circles group discussion (LCGD) in the teaching of "Self-directed Learning of English Reading" course, and analyze whether the LCGD can effectively improve the English reading ability and the interest of senior high school students in extracurricular reading for assisting students to establish a self-directed learning mode of English reading. This study adopted a pre-experimental research method of single-group pre-test and post-test design. Two semesters of LCGD Teaching were used to guide the subjects, and the difference between the pre-test and post-test scores were used to understand whether LCGD can be improved senior high school students’ English reading ability and interest in reading English books. Interviews were also conducted at the end of each semester to further explore students’ opinions and suggestions on the use of LCGD. The results indicated The LCGD cannot improve the learning abilities in a short period of time, but students believe LCGD can bring a sense of learning achievement and promote reading interest, and there is a significant difference in the pre-test and post-test results. Finally, according to the research results, some suggestions for English reading teaching are put forward.